Factors associated with external HIV-related stigma and psychological distress among people living with HIV in South Africa. (June 2021) - Ncitakalo, Nolusindiso; Mabaso, Musawenkosi; Joska, John; Simbayi, Leickness
Abstract: Background: HIV-related stigma and psychological distress among people living with HIV (PLHIV) pose a public health challenge in most African countries. This study aims to investigate the association between HIV-related stigmatizing attitudes and psychological distress amongst PLHIV in South Africa using the 2012 nationally representative population-based household survey. Methods: The data used in the analysis were collected using a multi-stage stratified cluster sampling design. Bivariate and multivariate logistic regression models were used to identify factors associated with stigma among PLHIV with psychological distress. A total of 2521 HIV positive individuals that responded to the question on psychological distress, 34.3% had psychological distress and 37.9% experienced high levels of HIV related stigmatizing attitudes. Stigmatizing attitudes among PLHIV with psychological distress were significantly less likely among those with secondary level education [aOR = 0.67 (95% CI: 0.44–1.01), p = 0.050], those with correct knowledge about HIV and rejection of myths about HIV [aOR = 0.58 (95% CI: 0.38–0.89), p = 0.013], and those who ever tested for HIV [aOR = 0.65 (95% CI: 0.42–1.01), p = 0.054]. Conclusion: The findings suggest a need to reinvigorate stigma-reduction interventions in the national HIV response with emphasis on HIV awareness and education campaigns. In addition, HIV testing services should be reinforced through communication strategies targeted against HIV stigmatization, discrimination and fear. There is also a need to continuously engage PLHIV in programs through counselling and support interventions for acceptance of HIV positive status and to help them cope with HIV-related stigma. Highlights: Stigmatising attitudes were more likely in older age group compared to the youth. Stigmatising attitudes were less likely among those with higher levels of educational attainment. Stigmatising attitudes were more likely among others race groups compared to Black Africans. Stigmatising attitudes were more likely among those residing in rural / farm areas compared to urban areas.